A Chebyshev wavelet operational method for solving stochastic Volterra-Fredholm integral equations - Mohammadi, Fakhrodin (International Journal of Applied Mathematical Research, 2015)
In this paper‎, ‎the stochastic operational matrix of Ito -integration for the Chebyshev wavelets is applied for solving stochastic Volterra-Fredholm integral equations‎. ‎The main characteristic of the presented method is that it reduces stochastic Volterra-Fredholm integral equations into a linear system of equations‎. ‎Convergence and error analysis of the Chebyshev wavelets basis is considered‎. ‎The efficiency and accuracy of the proposed method was demonstrated by some non-trivial examples and comparison with the other existing methods.